Students’ learning styles among bachelor of science in information studies (Hons) (Library and Information Management) (IM224) in UiTM Kedah / Muhammad Faizal Iylia Mohd Ghazali - Mohd Ghazali, Muhammad Faizal Iylia (Faculty of Information Management, 2012)
There has been much discussion about learning styles among students nowadays. Research regarding the learning styles has primarily emphasized the importance factor of their behaviours, technology and environment factor. Those listed are among factor that affect student learning styles. Actual surveys are taken from among the new Bachelor of Science in Information Studies (HONOURS) Library and Information Management (IM224) at UiTM Kedah. Which are used to illustrate between the learning styles and their learning performance.